Engaging primary care professionals in OECD's international PaRIS survey: a documentary analysis - Candan Kendir; Michael van den Berg; Janika Bloemeke-Cammin; Oliver Groene; Frederico Guanais; Andree Rochfort; Jose M. Valderas; Niek Klazinga (BMC, 2024)
Abstract Healthcare professionals have first-hand experience with patients in clinical practice and the dynamics in the healthcare system, which can be of great value in the design, implementation, data analysis and dissemination of research study results. Primary care professionals are particularly important as they provide first contact, accessible, coordinated, comprehensive and continuous people-focused care. However, in-depth examination of the engagement of health professionals in health system research and planning activities-how professionals are engaged and how this varies across national contexts- is limited, particularly in international initiatives. There is a need to identify gaps in the planning of engagement activities to inform the design and successful implementation of future international efforts to improve the responsiveness of health systems to the changing needs of patients and professionals. The aim of this study was to explore how primary care professionals were engaged in the design and implementation plans of an international health policy study led by the Organisation for Economic Co-operation and Development (OECD). The OECD's international PaRIS survey measures and disseminates information on patient-reported outcome and experience measures (PROMs and PREMs) of people living with chronic conditions who are managed in primary care. A documentary analysis of 17 written national implementation plans (country roadmaps) was conducted between January and June 2023. Two reviewers independently performed the screening and data abstraction and resolved disagreements by discussion. We reported the intended target primary care professionals, phase of the study, channel of engagement, level of engagement, and purpose of engagement. All 17 countries aimed to engage primary care professionals in the execution plans for the international PaRIS survey. While organisations of primary care professionals, particularly of family doctors, were the most commonly targeted group, variation was found in the timing of engagement activities during the different phases of the study and in the level of engagement, ranging from co-development (half of the countries co-developed the survey together with primary care professionals) to one-off consultations with whom. International guidance facilitated the participation of primary care professionals. Continuous collaborative efforts at the international and national levels can foster a culture of engagement with primary care organisations and individual professionals and enhance meaningful engagement of primary care professionals.